Dimensions of private law : categories and concepts in Anglo-American legal reasoning / Stephen Waddams. - Waddams, S. M. (Cambridge University Press, 2003)
Anglo-American private law (the law governing mutual rights and obligations of individuals) has been a far more complex phenomenon than is usually recognized. Attempts to reduce it to a single explanatory principle, or to a precisely classified or categorized map, scheme, or diagram, are likely to distort the past by omitting or marginalizing material inconsistent with proposed principles or schemes. Many legal issues cannot be allocated exclusively to one category. Often several concepts have worked concurrently and cumulatively, so that competing explanations and categories are not so much alternatives, of which only one can be correct, as different dimensions of a complex phenomenon, of which several may be simultaneously valid and necessary. This 2003 study will be of importance to those interested in property, tort, contract, unjust enrichment, legal reasoning, legal method, the history of the common law, and the relation between legal theory and legal history.